FAKTOR–FAKTOR YANG MEMENGARUHI KOMITMEN AFEKTIF ORGANISASI PEGAWAI DINAS KESEHATAN - Syafrizal Amin Nasution (Fakultas Kesehatan Masyarakat Institut Kesehatan Deli Husada Delitua, 2019)
This study aims to the factors that influence organizational affective commitment among employees of health office of deli serdang district 2015. This research is a quantitative survey with cross sectional study . The population in this study were employees of the District Health Office Deliserdang In 2014 as many as 120 people and a sample of 120 people. Data analysis method by means of univariate, bivariate analysis with chi square test and multivariate analysis with multiple logistic regression test. The results showed statistically motivation and satisfaction associated with affective organizational commitment of employees the District Health Office Year 2015. Age, Educationis and long of work was not associated with affective organizational commitment of employees. Results Deliserdang multiple logistic regression test unknown variables that influence the affective organizational commitment to employee motivation and working conditions.